Cultura do trabalho de desenvolvedores de software livre - Mello, Matheus Guimarães (2016)
This research aims to understand the possible relationship between hacker ethics and its sociability (a continuous product of socialization and life trajectories) with organizational culture (or culture du travail in French sociology literature) of Free and Open Source Software (FOSS) developers. It is based on the assumption that the expansion of the Information Technologies (IT) in the last two decades should not be de-contextualized from recent capitalism’s restructuring of and its consequences. The increase of precarity in labour relations is a major ongoing process, by which companies throughout the world emphasizes flexible work contracts, short-term projects and outsourcing. In this context, IT organizations play labour relations a pivotal role, as they handle the information for the new forms of work managing. At the same time, working in IT is, since its emergence, adapted to the flexibility scheme. Nevertheless, the development of FOSS is inseparable from its original hacker ethics. The hypothesis is that the values of sharing knowledge and peer working of the hacker culture is significant to understand the relationship between developers’ continuous processes of socialisation (identities formation) and the organizational culture of the company/foundation. The study will focus whether there are conflicts, negotiations and adaptations between the developers’ previous values and the manner they arrange their collective work. Thereby, the goal is to understand technology, culture and work as a whole. To this end, semi-structured interviews (during an exploratory and a complementary stages) and a virtual survey among Brazilian FOSS developers will be conducted. These will consider the life course (and socialisation) as the main analytical unit, since it highlights the people who embody a culture of sharing and also stands behind the technique.